Gamma Tomography as The Complementary Technique for Pipe Scale Investigation: Field Experiment at Petrochemical Plant - Bayu Azmi; Indra Milyardi; Megy Stefanus; Wibisono Wibisono; Fery Hadi Setiawan; Norman Pamungkas; Zulkifli Lubis (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2023)
Crack gas flowing from furnace to gasoline fraction tower through BA-106 pipeline. The pipeline has not been inspected for 30 years of operation and it is suspected that there is pipe scale in it. The scaling reduces the inner diameter of the pipe which disrupt the pipeline flow rate that might cause a fatal accident. The scale particles also became impurities in the subsequent process. The information on scale conditions inside the pipeline is needed to determine further action to ensure safety and maintain the productivity of the plant. The gamma scanning technique was conducted at 18 points to diagnose the scaling profile inside the pipe. A collimated 2.96 GBq 137Cs radiation source emits a pencil beam of gamma photons to penetrate the pipe. A NaI(Tl) scintillation detector was placed opposite the gamma source to detect the photons. They were moving in parallel vertically and horizontally for every 10 mm step to get the attenuation profile of the pipe. Furthermore, a tomography scan was performed at selected points with 32 projections data. So far previous experiments were performed in the laboratory and the objects were smaller (less than 500 mm), however, the current experiment was performed in real industrial plants and the object diameter was about 1500 mm. The reconstructed image has been successful in showing the cross-sectional of the pipe that consists of scale inside it. The image was analyzed to get the percentage of the remaining fluid area due to scaling. The remaining fluid area was 56.15% of normal pipe without scale. It was proved that the gamma tomography technique is suitable for pipe scale measurement to get the cross-section visualization of the pipe.